2020
DOI: 10.3390/ani10112170
|View full text |Cite
|
Sign up to set email alerts
|

Transport, Associated Handling Procedures and Behaviour of Calves Marketed through Chilean Auction Markets

Abstract: In Chile, selling animals through livestock markets is common. At markets, stressful events like loading, unloading and travel are at least duplicated. We described procedures associated with transport of calves at 20 markets and evaluated compliance with Chilean law by performing a survey of drivers who transport calves from origin farms to markets (OM) and from markets to destination (MD). During loading and unloading, we evaluated handling by stockpersons, facilities, fitness for transport, and behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…In agreement with our findings, Bergin and Nijman [ 30 ] found that animals kept in Moroccan markets showed poor welfare conditions due to lack of water access, sun/heat protection, and facilities to hide from stressors. Similar welfare issues have been found with cattle kept at markets in South America [ 31 ] and small ruminants in a large abattoir in Ethiopia [ 32 ]. Pritchard et al [ 33 ], using skin tenting in a large sample of equids in the Middle East, found that 37% of donkeys and 50% of horses showed signs of dehydration.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement with our findings, Bergin and Nijman [ 30 ] found that animals kept in Moroccan markets showed poor welfare conditions due to lack of water access, sun/heat protection, and facilities to hide from stressors. Similar welfare issues have been found with cattle kept at markets in South America [ 31 ] and small ruminants in a large abattoir in Ethiopia [ 32 ]. Pritchard et al [ 33 ], using skin tenting in a large sample of equids in the Middle East, found that 37% of donkeys and 50% of horses showed signs of dehydration.…”
Section: Discussionsupporting
confidence: 68%
“…Any stress effects resulting in a reduction in the quality of the meat must be minimized. Poultry is most exposed to the stress of being caught on farms, transported, and then taken to the slaughterhouse and hooked before stunning [7,25]. The warm summer months are particularly problematic during transport, when high temperatures during transport can lead to overheating of poultry and subsequent death during transport or deterioration of meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigators have found elevated creatine kinase levels upon arrival (Van de Water et al, 2003;Grigor et al, 2004;Earley et al, 2010;Bernardini et al, 2012). However, the results of another study indicated that there were no significant changes in CK activity following transport (Cafazzo et al, 2012).…”
Section: Thwarted Lying Intentionsmentioning
confidence: 96%
“…Unweaned calves are more difficult to move than older cattle because they do not show a natural herding behaviour (Broom and Fraser, 2007), thereby increasing the risk of poor handling (Roadknight et al, 2021a) and injury, discomfort and pain during handling. Gregory et al (2013) suggested that slips and falls were the main problems during loading, and according to Bravo et al (2020) slips and vocalisations were most frequently observed during unloading, whereas slips and turning around happened most frequently during loading.…”
Section: Vi) Handling Unweaned Calvesmentioning
confidence: 99%